Development of semi-fluidized bed bioreactor as novel bioreactor system for the treatment of palm oil mill effluent (POME) - Alad, Abass O.; Jameel, Ahmed Tariq; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail; Alam, Md. Zahangir (2011)
Palm oil mill effluent (POME) is a high strength organic wastewater, which adversely affects the aquatic life as well as the human life directly or indirectly. This has attracted concern due to the rapid expansion of the oil palm industries in countries such as Malaysia and Indonesia, which currently contribute about 80% of the world palm oil. The conventional treatment techniques used over the past decades includes various bioreactors such as Pond digester, Anaerobic filtration, Up-flow anaerobic sludge blanket (UASB), Up-flow anaerobic sludge fixed-film (UASFF) , Continuous stirred tank reactor (CSTR), Anaerobic contact digestion and Fluidized bed. These bioreactors are largely operated anaerobically and have been reported to be less effective for the treatment of the increasing volume of POME as well as meeting the new stringent wastewater standards. Therefore, treatment method such as aerobic under a continuous system is anticipated to be effective alternative to the defects observed in the previously employed bioreactors. The use of semifluidized bed bioreactor containing immobilized cells for the biodegradation of various high strength organic wastewater have been reported as highly efficient treatment method. Thus, in order to address the increasing environmental impact of POME in the palm oil producing nations, the application of semifluidized bed bioreactor as a novel technology in the palm oil industry will be of immense benefit, economically and environmentally.